A clinical study on types of ocular injuries following road traffic accidents in a tertiary health care hospital in Chennai, Tamil Nadu - Frederick, Melvin; Kumaresan, Vinisha; Anuradha, P. (International Journal of Advances in Medicine, 2022)
Background: Ocular injuries are one of the major causes of preventable blindness, most common cause being road traffic accidents (RTA). More than 90% of eye injuries can be prevented by simple measures. The main aim of this study is to find out the type of ocular injuries following RTA, and to find out the association between the type of injury and the vehicle they rode during the RTA. Methods: This cross-sectional study was conducted at Saveetha medical college and hospital, Chennai. It comprised of 160 patients who presented to the department of ophthalmology and emergency with ocular injuries following RTA. A detailed trauma history from the patient was taken and examination was done to assess the type, location, and the severity of the ocular injury. Analysis was done using SPSS software. Results: Among the 160 patients, periorbital ecchymosis was the most common type of ocular injury (27.5%). Males were more affected (85%), 2-wheeler accidents being the most common one (85%), with most of the injuries with unilateral eye involvement (87.5%). Conclusions: Most of the ocular injuries following RTA were injuries in and around the eyelid, which can be easily prevented by simple measures like wearing helmet, maintaining the speed limit and observation of traffic rules.